The ethics of financial speculation in futures markets - Ingo Pies; Matthias Georg Will; Thomas Glauben; Sören Prehn (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2013)
This article sketches an ethics of (financial) speculation in futures markets. (1) It identifies an intentionalistic fallacy prevalent in moral criticisms of speculation in general and of financial speculation in particular. (2) It scrutinizes the degree to which the recent debate on financial speculation with agricultural commodities follows the general pattern of moral criticism and its intentionalistic fallacy. (3) It then provides a theoretical and empirical in-depth analysis of long-only index funds engagement in futures markets and concludes that moral criticisms which put them in the pillory as "hungermakers" are unjust(ified). This proves that ethics, understood as a theory of morality, can criticize moral criticisms of financial speculation on moral grounds. (4) Finally, this article discusses the option of interdisciplinary cooperation between ethics and economics. – – Dieser Artikel skizziert eine Ethik der finanziellen Spekulation auf Terminmärkten. (1) Er identifiziert einen intentionalistischen Fehlschluss, den man in vielen Ansätzen moralischer Kritik der Spekulation im Allgemeinen und der Finanzspekulation im Besonderen nachweisen kann. (2) Untersucht wird, bis zu welchem Grad die jüngste Diskussion um Finanzspekulation mit Agrarrohstoffen den generellen Mustern moralischer Kritik folgt, einschließlich des intentionalistischen Fehlschlusses. (3) Anschließend erfolgt eine ausführliche theoretische und empirische Analyse der Terminmarktgeschäfte von Long-only-Indexfonds. Sie gelangt zu dem Ergebnis, dass die moralische Kritik, welche diese Indexfonds als "Hungermacher" an den Pranger stellt, ungerecht(fertigt) ist. Dies zeigt, dass Ethik in der Lage ist, die moralische Kritik an der Finanzspekulation mit moralischen Argumenten zurückzuweisen. (4) Dieser Artikel endet mit einer Reflexion über die mögliche interdisziplinäre Zusammenarbeit zwischen Ethik und Ökonomik.
urn:nbn:de:gbv:3:2-23087
Keywords: A12; D84; G23; P34; Q14; Q18; 330; ethics; speculation; financial speculation; futures market; agricultural commodities; index funds; moral criticism; Ethik; Spekulation; Finanzspekulation; Terminmarkt; Agrarrohstoffe; Indexfonds; moralische Kritik